An Overview of Basic Concepts of Finite Element Analysis and Its Applications in Orthodontics - Rastegari, Shafagh; Hosseini, Seyed Majid; Hasani, Mojtaba; Jamilian, Abdolreza (The Journal of Dentists, 2023)
Purpose: The aim of this article is to acquaint the readers with the aims and goals of the finite element method and how to use it in dentistry and especially in orthodontics. Methods: The finite element method (FEM) has shown to be a beneficial research tool that has assisted scientists in various analyses such as stress-strain, heat transfer, dynamic, collision, and deformation analyses. The FEM is responsible for predicting the behavior of objects under different working conditions. It is a computational procedure to measure the stress in an element, which performs a model solution to solve a problem; the FEM subdivides a large system into smaller, simpler parts called finite elements. This is achieved by a particular space discretization in the space dimensions, which is implemented by the construction of a mesh of the object. The technique of FEA lies in the development of a suitable mesh arrangement. Conclusions: The FEM can be effective in understanding the behavior of teeth, both jaws, craniofacial structure, and other hard tissue structures of humans under various working conditions, as the technique allows for evaluating tooth movement and the stress distribution within the surrounding alveolar bone, the periodontal ligament (PDL). This technique is exceptionally valuable for evaluating mechanical aspects of biomaterials and human tissues that can hardly be measured in vivo. This review article presents the FEM, its methodology, and its application in the orthodontic domain.